How to Build a Plant Lighting System - Sydney Park Brown; Kathleen C. Ruppert; Kalmer D. Hendry; Bart Schutzman (EDIS, 2007)
Revised! Circular 1137, a 7-page illustrated publication by Sydney Park Brown, Kathleen C. Ruppert, Kalmer D. Hendry, and Bart Schutzman, provides detailed, easy-to-follow instructions for building an inexpensive, portable plant lighting system. Published by the UF Department of Environmental Horticulture, September 2007.